2021
DOI: 10.5194/acp-2021-79
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement report: In situ observations of deep convection without lightning during the tropical cyclone Florence 2018

Abstract: Abstract. Hurricane Florence was the sixth named storm in the Atlantic hurricane season 2018. It caused dozens of deaths and major economic damage. In this study, we present in situ observations of trace gases within tropical storm Florence on September 2, 2018 after it had developed a rotating nature, and of a tropical wave observed close to the African continent on August 29, 2018 as part of the research campaign CAFE Africa (Chemistry of the Atmosphere – Field Experiment in Africa) with the HALO (High Altit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…NO concentrations varied between 0.005 and 0.56 ppbv for MF10 and between 0.005 and 0.46 ppbv for MF12. We have recently shown that enhanced NO concentrations in the morning and afternoon of MF12 were due to local, recent light- ning activity (Nussbaumer et al, 2021). For MF10, enhanced NO concentrations at high altitudes had their source over the African continent.…”
Section: Influence Of Atmospheric Water Vapormentioning
confidence: 98%
“…NO concentrations varied between 0.005 and 0.56 ppbv for MF10 and between 0.005 and 0.46 ppbv for MF12. We have recently shown that enhanced NO concentrations in the morning and afternoon of MF12 were due to local, recent light- ning activity (Nussbaumer et al, 2021). For MF10, enhanced NO concentrations at high altitudes had their source over the African continent.…”
Section: Influence Of Atmospheric Water Vapormentioning
confidence: 98%
“…NO concentrations varied between 0.005 and 0.56 ppbv for MF10 and between 0.005 and 0.46 ppbv for MF12. We have recently shown that enhanced NO concentrations in the morning and afternoon of MF12 were due to local, recent lightning activity (Nussbaumer et al, 2021). For MF10, enhanced NO concentrations at high altitudes had their source over the African continent.…”
Section: Influence Of Atmospheric Water Vapormentioning
confidence: 98%